1992
DOI: 10.1103/physrevlett.68.702
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy and magnetic field dependence of the planar copper NMR spin-lattice relaxation rate in the superconducting state ofYBa2Cu

Abstract: The authors report measurements of the planar 63 Cu nuclear spin-lattice relaxation rates 63 H / u / ( 63 W| r ) for the static field oriented along the a (c) axis in the superconducting state of YBa2Cu307. These measurements were made on a single sample as a function of temperature and magnetic field. The weak-field results are well explained by several recent calculations in terms of a BCS spin-singlet, orbital-d-wave pairing state. They also find that at low temperatures bi W\ c varies linearly with the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(26 citation statements)
references
References 15 publications
1
24
1
Order By: Relevance
“…Furthermore, the parameter values which are required are consistent with what is known about the Fermi surface [19][20][21] and spin-fluctuations from other measurements [6,7]. The analysis is based, however, on the subtraction of a constant relaxation rate from both quantities, an approach which must be justified within microscopic theory; we present a brief discussion of these issues and the light shed by our analysis on the behavior of the low-energy impurity scattering amplitude.…”
mentioning
confidence: 54%
“…Furthermore, the parameter values which are required are consistent with what is known about the Fermi surface [19][20][21] and spin-fluctuations from other measurements [6,7]. The analysis is based, however, on the subtraction of a constant relaxation rate from both quantities, an approach which must be justified within microscopic theory; we present a brief discussion of these issues and the light shed by our analysis on the behavior of the low-energy impurity scattering amplitude.…”
mentioning
confidence: 54%
“…One of the first indications of a contribution to relaxation from vortices was obtained from the field dependence and from the orientation dependence of 63Cu R~ in oriented powders of YBCO and LaSCO [21,22]. It was tentatively concluded that in the low temperature range the contribution comes from relaxation of nuclei from within the vortex core and subsequent spin diffusion to nuclear spins outside the core.…”
Section: Rlsmentioning
confidence: 98%
“…However, less attention has been payed on the ratios of these rates [2][3][4][5][6][7][8][9] in the superconducting state. A difficulty arises since in the normal state, the spin-lattice relaxation is largely insensitive to the strength of the applied magnetic field [10,11], while the relaxation rate becomes field dependent in the superconducting state at low temperature, with 1c [5][6][7]12]. In order to draw any conclusions about magnetism in the superconducting state it is therefore very important to look for intrinsic effects which can only be obtained from experiments done in weak magnetic fields so as to minimise the flux line influence.…”
Section: −1mentioning
confidence: 99%